Implementation of Educational Games Using the Levenshtein Distance Algorithm for Improving Elementary School Students' Word Vocabulary Android - Rio Dwi Cahya; Nenna Irsa Syahputri (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
The low motivation of elementary school students in learning Indonesian vocabulary through conventional methods is needed, so an innovative technology-based approach is needed that is able to combine elements of learning and entertainment. Scramble educational games are designed with a mechanism of randomizing letters from a word that must be rearranged by students into correct words. In the answer validation process, the Levenshtein Distance algorithm is used to measure the error rate based on the minimum number of edit operations (substitution, insertion, or deletion) required for the guessed word to be equal to the target word. With the application of this algorithm, the system is not only able to provide a binary right or wrong assessment, but also assess the degree of closeness of students' answers to the supposed word. This allows for more adaptive and educational feedback, such as